Evaluation of the Congenital Hypothyroidism Detection Strategy in Extremely Preterm Infants in Western Andalusia - Rubio-Sánchez, Ricardo; Núñez-Jurado, David; Melguizo-Madrid, Enrique; Álvarez-Ríos, Ana I.; Delgado-Pecellín, Carmen (American Journal of Perinatology, 2021)
Objective This study aimed to identify extremely premature infants (< 31 weeks of gestation and/or <1,500 g) affected by congenital hypothyroidism (CH) with delayed elevation of thyrotropin (TSH) and to evaluate the detection strategy for this pathology in our reference screening population.Study Design A descriptive and retrospective study was carried out with samples collected from western Andalusia and the autonomous city of Ceuta.Results This protocol allowed us to detect six neonates with delayed TSH elevation. One of them, due to serious heart problems, died without being able to confirm CH. In two neonates, however, it was possible to detect CH, another two presented a persistent TSH elevation but normal free T4, and another one presented a temporary TSH elevation.Conclusion It is essential to repeat the CH screening in extremely premature infants, not only at the age of 15 days but also with a third sample at the moment of hospital discharge to detect cases with delayed TSH elevation.Key Points
Keywords: congenital hypothyroidism; extremely preterm infants; neonatal screening; TSH; FT4